(untitled) (Analysis of International Sciences, 2024)
The innovative path of human development is characterized by the active use of information technology in any field. This is due to the rapid development of high technologies and, accordingly, with the advent of new data analysis tools. One of the rapidly developing areas of application of information technology, to which there is great interest in society, the state, commercial organizations, is high-quality forecasting.